2018
DOI: 10.5650/jos.ess18067
|View full text |Cite
|
Sign up to set email alerts
|

Stability Evaluations of Different Types of Vegetable Oil-based Emulsions

Abstract: inflammatory 5 and antioxidant 6 properties. Therefore, it is suitable to be used in food, pharmaceutical and cosmetic industries. Soybean oil SBO is extracted from Glycine max seeds Fabaceae. It is a popular edible oil used in baking, salad dressing and cooking. It contains high percentage of essential fatty acids, polyunsaturated fatty acids and minor constituents, such as vitamins, isoflavones, tocotrienols and phytosterols. Previous studies showed that it possessed extensive medicinal properties, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Palm olein (POo), olive oil (OO), safflower oil (SAF), grape seed oil (GSO), soybean oil (SBO) and sunflower oil (SFO), which have different saturation levels, are the main oils in the stability evaluation study of various vegetable oil‐based emulsions. As a result, it was confirmed that the saturation level of the vegetable oil had a significant effect on the emulsion stability 30 …”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Palm olein (POo), olive oil (OO), safflower oil (SAF), grape seed oil (GSO), soybean oil (SBO) and sunflower oil (SFO), which have different saturation levels, are the main oils in the stability evaluation study of various vegetable oil‐based emulsions. As a result, it was confirmed that the saturation level of the vegetable oil had a significant effect on the emulsion stability 30 …”
Section: Resultsmentioning
confidence: 70%
“…As a result, it was confirmed that the saturation level of the vegetable oil had a significant effect on the emulsion stability. 30 There is a study result that Korean red ginseng hot water extract relieved atopic dermatitis-like inflammatory response by negative regulation of the mitogen-activated protein kinase (MAPK) signaling pathway in vivo.…”
Section: Good Ingredients For Vegan and Vegan Cosmetics Originated Fr...mentioning
confidence: 99%
“…In this case, the formulation becomes less stable when subjected to centrifugal force. Literature data showed that creaming was observed in vegetable oils including olive, safflower, grape seed, soy bean and sunflower oils-based emulsions that kept at 40 after a 14-day of the experimental period 23 . The data postulates that the stability of PPFObased emulsion is superior to the vegetable oil-based emulsions though the performance of PPFO-based emulsion is a little poor compared to that of PO-based emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…The emulsions were prepared according to Teh et al 2018 23 . In brief, oil-soluble ingredients, stearic acid 20 g , cetyl alcohol 20 g and glycerol monolaurate 30 g were first added into 300 g of PPFO, then mixed and heated at 70 until fully dissolved.…”
Section: Preparation Of Emulsionmentioning
confidence: 99%
See 1 more Smart Citation